Kepastian Hukum Pengambilalihan Saham (Akuisisi) Perseroan Terbatas Tertutup Dengan Akta Jual Beli Saham - Feby Wulandari, Lifia (Recital Review, 2021)
The practice in the world of notary that uses the Deed of Sale and Purchase of Shares in the event of a stock acquisition is a legal issue that underlies the occurrence of this research. The sale and purchase of shares and the acquisition of shares in notarial practice which are often equated cause problems in practice, in line with the duties of the notary office in making deeds, this will lead to multiple interpretations in making the Notary deed. There is no specific regulation that underlies this, so there needs to be a discussion about what the position of the legal issue is. The research method uses a normative juridical research type, with a statutory approach, a case approach, a historical approach, and a conceptual approach. The results of this research are: regarding the use of the Deed of Sale and Purchase of Shares, it can be done as long as there is no change in control, but if in practice the sale and purchase of shares results in a transfer of control, it should be carried out through procedures, terms and procedures for takeover of shares (acquisition). The legal position is closely related to the role of the notary in making deeds, which must always minimize the existence of the deed from any problems in the future. Legal certainty of share takeover (acquisition) of a Limited Liability Company with a Share Sale and Purchase Deed, where the sale and purchase of shares does not result in a change in controlling of shares, the use of the sale and purchase deed provides certainty for the parties therein, but if the sale and purchase of shares results in the occurrence of changes in share controllers, then the sale and purchase deed does not provide legal certainty for the parties in it, it should be done in accordance with the procedures and mechanisms governing share acquisition.